BAGAIMANA IDIOM MEMENGARUHI KEPUASAAN PENONTON DALAM FILM ‘THE TRUMAN SHOW’ - Sufina Zahra Rambe; Uswatun Hasanah Lubis; Fathia Naziva; Nashwa Hawanu Fero (Indonesian language and literature education program Majapahit Islamic University, 2025)
This work analyzes how idioms in The Truman Show influence the psychological response of audience. The analysis uses Boatner & Gates semantics theory in order to provide the theoretical background regarding idioms while using Leon Festinger's theory of Cognitive Dissonance to draw the psychological connection. Although there are many studies on semantics and psychological dissonance, there has yet to be a study that connects semantics and psychological response through the Truman Show. Using a descriptive qualitative method, 25 idioms were identified from the movie script: Lexemic idioms (44%), Phrase idioms (24%), Frozen idioms (24%), and Proverbs (8%). The dominance of Lexemic idioms requires audiences to interpret both literal and figurative meanings which evokes their psychological engagement. Keywords: Idioms, Cognitive dissonance, Semantics